CFD Investigation of Different Flow Field Designs for Efficient PEMFC Performance - İmdat Taymaz; Safiye Nur Özdemir (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Proton exchange membrane (PEM) fuel cell performance depends substantially on the geometry, configuration of the flow channels, and size. A right gas flow field pattern requires a homogeneous reactant distribution, low-pressure drop, and good water management. This paper outlines a numerical study, investigated the influence of the U-type, Z-type, and serpentine flow field configuration on the steady-state cell performance using the CFD technique ANSYS FLUENT PEMFC module. The main goal of this study focuses on a novel perspective for enhancing the design of the PEMFC resulting in better performance. The results indicate that the PEMFC with serpentine flow field configuration yields a significantly higher power density compared to the other designs.